Out-of-Field Public Senior High School Teachers: Competencies in Teaching Physical Education - John Clark Martos Mesias (CV Rezki Media, 2022)
Background: Making sure that Physical Education (PE) classes are staffed with qualified and trained PE teacher is the most indispensable ingredient to a quality PE program. Only certified PE teachers should be given the accountability of teaching the skills and giving instruction that our young people need to adopt and maintain a physically active routine. Objectives: The purpose of this qualitative study was to draw out the lived experiences of out-of-field public Senior High School teachers on teaching Physical Education, identify the trainings and seminars’ relevant to their professional development and advancement. Methods: Through the descriptive narrative method, 22 out-of-field public senior high school teachers who were teaching PE from Areas 2A and 2B in Leyte Division served as participants and results derived from the interviews were coded and transcribed to come up with themes and sub-themes that follows: content knowledge with sub-themes; mastery of skills taught, sports-related trainings and dance pedagogy; pedagogical skills with sub-themes promotion of cooperative learning, stimulation of assigning leaders per group activities, inclusion of appropriate assessment tool or rubrics, and assurance of learners’ safety. Results: The study confirms that mastery of subject discipline is essential to a teacher. Teaching PE subjects is more than the theory; it delves more on skills demonstration and acquisition. If teachers are expert in the field they teach, they can demonstrate the skills, clearly answer students’ questions, and lessen the workload as they have but minor adjustment as far as the subject matter is concerned. Conclusion: This study confirms that mastery of the content is essential in the teaching-learning process. Teaching PE subjects is not all about imparting the content of the subject theoretically; it more on skills demonstration and acquisition.